Banking Competition and Capital Ratios - Cihak, Martin (IMF Working Papers; Working Paper ;, 2007)
We use data for more than 2,600 European banks to test whether increased competition causes banks to hold higher capital ratios. Employing panel data techniques, and distinguishing between the competitive conduct of small and large banks, we show that banks tend to hold higher capital ratios when operating in a more competitive environment. This result holds when controlling for the degree of concentration in banking systems, inter-industry competition, characteristics of the wider financial system, and the regulatory and institutional environment.